How to Attract Air Freight Business: Defining Critical Success Factors for Regional Airports - David M. Herold; Simon. Wilde; Natalie Wojtarowicz (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Much less is known about the numerous smaller airports that collectively comprise the majority of aviation networks. A process of deregulation has left small Australian airports in the hands of local governments, with as many as 50 per cent are reporting an operating loss each year. The integration of an air cargo sector and establishing a freight value proposition can add a competitive advantage to a regional airport. Airports such as Memphis, Louisville or Dubai have grown through their close relationship with global cargo companies (like FedEx or UPS), or through manufacturing companies moving closer to the airport. Accordingly, the ability to attract carriers and air cargo traffic is crucial to the establishment of a transport and logistics hub An airport with an emerging freight hub is therefore likely to experience substantial economic growth from the freight industry, not only for the airport itself, but also for the host region. There is little research on regional airports, however the literature suggests that the most important points of attracting air freight as external factors and are outside the airport's influence. There is a need to create demand by the development of important industry clusters around airports. This means an involvement of third parties to develop the airport and its region to achieve appropriate levels of market demand and drive down the (lack of) economics of scale. The aim of this paper is to give an overview about the literature and describes in which environment Australian regional airports currently operate.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; sustainability; regional airports; air freight; success factors